Impact of Governance on Financial Development: evidence from West Africa - Abubakar, Yahaya Ibrahim; Mustapha, Rafiu Ayobanji; Ajiboye, Emmanuel Shola (Faculty of Economics and Business, Hasanuddin University, 2020)
The study explores the impacts of governance on financial development in West African countries.Data for the study were obtained from the World Bank Database covering the period from 2006-2017. The variables for governance comprises of the six world governance indicators while financial development was represented by ratio of bank deposit to GDP and domestic credit to private sector. The control variables included in the model are interest rate, inflation, GDP per capita and trade openness. The findings from the study revealed that political stability and absence of violence, and regulatory quality have significant effects on both proxies of financial development. Also, voice and accountability, trade openness and interest rate show significances on the ratio bank deposit to GDP while government effectiveness (negative), rule of law, and control of corruption show significances on domestic credit to private sector. Thus, improving the quality of governance through strengthening legal and institutional frameworks, enforcement of standards and empowering of supervisory agencies, introducing an efficient regulatory environment to facilitate financial inclusion will play significant roles in the pace of financial development in the West Africa region. Keywords: Governance, Financial Development and West Africa